IMPORTANT ROLE OF GAS STATIONS OPERATOR AND THE REASON FOR OWNERS SHOULD TREAT THEM FAIRLY - Rosidah, Selly; Soetjipto, Budi W. (Universitas Brawijaya, Indonesia, 2017)
The operator of gas stations have an important role in providing services to consumers. Gas station owners have to look at the position as a provider of human resources that need to be considered. However, many gas station operators who feel injustice in terms of remuneration, distribution of working hours, job guarantees, and the treatment gas station owner. This study aimed to determine the effect of distributive injustice and interactional justice on job satisfaction and employee engagement. The object of this study was Pertamina gas station employee who served as an operator in Jakarta. Data were taken from 200 respondents who are gas stations operator of the five areas in Jakarta. The data in this study used the statistical method of SEM with LISREL statistical program. The results showed that perceptions of interactional justice have an influence on a job satisfaction gas stations operator, job satisfaction affects the employee engagement, and there is no relationship between distributive justices on job satisfaction.